Registration of three peanut allotetraploid interspecific hybrids resistant to late leaf spot disease and tomato spotted wilt. Issue 3 (20th August 2021) - Chu, Ye; Stalker, H. Thomas; Marasigan, Kathleen; Levinson, Chandler M.; Gao, Dongying; Bertioli, David J.; Leal‐Bertioli, Soraya C. M.; Holbrook, C. Corley; Jackson, Scott A.; Ozias‐Akins, Peggy
Abstract: Cultivated peanut ( Arachis hypogaea L.) has a narrow genetic base and is isolated from its wild relatives. This genetic bottleneck results in a lack of strong resistance to biotic and abiotic stress. However, high levels of genetic variation and resistance exist among the wild relatives. In order to enlarge the genetic base of cultivated peanut and introgress beneficial alleles from the wild relatives, interspecific hybrids were produced among a set of selected diploid species. Upon colchicine treatment, fertile allotetraploids were recovered from three combinations including ( A. ipaënsis KG 30076 × A. correntina GKP 9530) 4x (Reg. no. GP‐241, PI 695391), ( A. ipaënsis KG 30076 × A. duranensis KGBSPSc 30060) 4x (Reg. no. GP‐242, PI 695392), and ( A. valida KG30011 × A. stenosperma V 10309) 4x (Reg. no. GP‐243, PI 695393). All of them demonstrated high levels of resistance to leaf spot diseases in the field. Tolerance to Tomato spotted wilt virus was found in ( A. valida KG 30011 × A. stenosperma V 10309) 4x . These newly created allotetraploids are cross‐compatible with cultivated peanut. These genetic resources will provide peanut breeding researchers with new sources of disease resistances to improve the agronomic performance of cultivated peanut. Core Ideas: These hybrids can broaden the genetic base of cultivated peanut by introgression. New synthetic allotetraploids from peanut wild relatives carry disease resistance. Synthetic allotetraploids are cross‐compatible with cultivated peanut.